SLAP Trial: Shock Wave Lithotripsy and Mechanical Percussion Therapy Post ESWL for Renal Calculi - Nishal Patel; Adrian Roe; Donna Stanton; Jay Roberts; Akshay Kothari (Advances in Urology)
Introduction and Objectives. ESWL is a popular treatment modality for small to medium sized renal calculi; however, the reported clearance rates especially in the lower pole have been poor. Mechanical percussion and inversion (MPI) therapy can be used as an adjunct to ESWL and has been shown to significantly improve stone clearance rates in several studies. In these studies, MPI therapy was administered in hospital by medical staff, requiring further hospital appointments with increased clinician and financial resources. Our objective was to evaluate whether patient-directed mechanical percussion and inversion (MPI) therapy performed at home after ESWL can improve stone-free rates compared with ESWL alone. Methods. We conducted a prospective randomised control trial. Included patients were males and females greater than 18 years of age with single or multiple ipsilateral renal calculi of total ≤10 mm on plain X-ray and noncontrast CT KUB. ESWL was performed at a single centre, at supine position under general anaesthesia with maximum 3000 shocks at a rate of 100 shocks per minute. Patients were discharged and randomised to either the control arm or MPI therapy. MPI therapy was self-directed in a home setting for 10 minutes a day, three times per week. Both arms had standard follow-up at 12 weeks with a plain X-ray KUB. Patients in the control group were offered cross over to the MPI arm after 12 weeks if residual stone fragments were detected. Statistical analysis was performed using SPSS software via Chi squared and Fisher’s exact tests. Ethical approval was obtained via the Prince Charles Hospital HREC Committee, HREC/2022/QPCH/84961. Results. 70 patients met inclusion criteria and underwent ESWL, and 5 were withdrawn. 33 patients were randomised to the MPI group and 32 to the control group. MPI significantly increased the stone clearance rate anywhere in the kidney (87.9% in the MPI group versus 59.4% in the control group, p=0.089), as well as the clearance rate in the lower pole (91.7% in the MPI group versus 63.2% in the control group, p=0.022). Delayed percussion did not improve the clearance rate over primary percussion p=0.835. Conclusion. This study has shown that MPI can be effectively performed in a home setting without the need for medical supervision and results in improved stone clearance rates post ESWL. The main limitations to the study were the use of X-ray over CT during the follow-up and variability in MPI compliance and administration. Further research is warranted into standardising home MPI protocols. This trial is registered with ANZCTR387061.